2021
DOI: 10.1515/cclm-2020-1701
|View full text |Cite
|
Sign up to set email alerts
|

Performance of digital morphology analyzer Vision Pro on white blood cell differentials

Abstract: Objectives Vision Pro (West Medica, Perchtoldsdorf, Austria) is a recently developed digital morphology analyzer. We evaluated the performance of Vision Pro on white blood cell (WBC) differentials. Methods In a total of 200 peripheral blood smear samples (100 normal and 100 abnormal samples), WBC preclassification and reclassification by Vision Pro were evaluated and compared with manual WBC count, according to the Clinical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 21 publications
4
14
0
Order By: Relevance
“…DI-60 on WBC preclassification showed high efficiency with verification in total samples; even in each group according to the WBC count ( Table 3 ). These results are similar to previous studies that evaluated the performance of DI-60, DM96, and Vision Pro [ 9 , 15 , 20 ]. However, DI-60 tended to show lower sensitivity with fewer WBCs in the sample for neutrophils, lymphocytes, and monocytes.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…DI-60 on WBC preclassification showed high efficiency with verification in total samples; even in each group according to the WBC count ( Table 3 ). These results are similar to previous studies that evaluated the performance of DI-60, DM96, and Vision Pro [ 9 , 15 , 20 ]. However, DI-60 tended to show lower sensitivity with fewer WBCs in the sample for neutrophils, lymphocytes, and monocytes.…”
Section: Discussionsupporting
confidence: 91%
“…According to the ICSH guidelines [ 21 ], mean difference or Bland–Altman plots should be evaluated in leukopenic, anemic or thrombocytopenic samples. In our previous study that evaluated a DM analyzer Vision Pro on WBC differentials, we found that the mean differences between the Vision Pro and manual count results were larger when analyzing only leukopenic samples than total samples [ 20 ]. Based on our previous study, we questioned and evaluated the analytical performance of DI-60 on WBC differentials in leukopenic samples, especially focusing on the precision.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations